2018
DOI: 10.1039/c8nr01540f
|View full text |Cite
|
Sign up to set email alerts
|

Silicon compatible Sn-based resistive switching memory

Abstract: Large banks of cheap, fast, non-volatile, energy efficient, scalable solid-state memories are an increasingly essential component for today's data intensive computing. Conductive-bridge random access memory (CBRAM) - which involves voltage driven formation and dissolution of Cu or Ag filaments in a Cu (or Ag) anode/dielectric (HfO2 or Al2O3)/inert cathode device - possesses the necessary attributes to fit the requirements. Cu and Ag are, however, fast diffusers and known contaminants in silicon microelectronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…[6,15,38] First-principles calculation indicates that active metal ions have low formation energy and migration barrier, for example, 1.02/0.72 eV for Ag + and 1.48/1.00 eV for Cu 2+ in HfO x matrix [39] ( Figure S1, Supporting Information), respectively. The HfO x is chosen as the model material in this work, as its high-κ feature usually leads to promising device performance in memristors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,15,38] First-principles calculation indicates that active metal ions have low formation energy and migration barrier, for example, 1.02/0.72 eV for Ag + and 1.48/1.00 eV for Cu 2+ in HfO x matrix [39] ( Figure S1, Supporting Information), respectively. The HfO x is chosen as the model material in this work, as its high-κ feature usually leads to promising device performance in memristors.…”
Section: Resultsmentioning
confidence: 99%
“…The HfO x is chosen as the model material in this work, as its high‐κ feature usually leads to promising device performance in memristors . First‐principles calculation indicates that active metal ions have low formation energy and migration barrier, for example, 1.02/0.72 eV for Ag + and 1.48/1.00 eV for Cu 2+ in HfO x matrix (Figure S1, Supporting Information), respectively. With the low activation energies and high electric field across the device (≈MV cm −1 ), metal ions will be injected heavily and rapidly from the electrodes into the dielectrics through hafnium vacancies, giving rise to overgrowth of the APC structure.…”
Section: Resultsmentioning
confidence: 99%
“…Since oxygen ions often have a higher diffusion barrier than silver and copper ions in oxide films, [45,90] highly stable quantum conductance states are thus more likely to be obtained in memristors with oxygen vacancy filaments. First, a thorough understanding on the physical origin of integer as well as half-integer quantum conductance is urgently required, which may serve as a guide for optimizing the performance of quantum conductance in memristors in future.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…This can be ascribed to the polarizability increasing in the series Ag→Ni→Pt, as well as higher charge numbers and sizes of Ni and Pt ions [78], which leads to their diffusion being difficult in switching layers. As such, Ag − /Cu − species can transport more easily in dielectrics [38] (especially Si [79]), which introduces defect centers into the integrated silicon circuitry [80]. Guha et al [79] employed first principles calculations for estimating diffusion barriers of active ions in HfO x .…”
Section: Electrode Engineeringmentioning
confidence: 99%
“…As such, Ag − /Cu − species can transport more easily in dielectrics [38] (especially Si [79]), which introduces defect centers into the integrated silicon circuitry [80]. Guha et al [79] employed first principles calculations for estimating diffusion barriers of active ions in HfO x . It is identified that Sn possesses a slower diffusion barrier without creating active defects, which reduces contamination risk than Cu and Ag.…”
Section: Electrode Engineeringmentioning
confidence: 99%